The role of TNCs in the extractive industry of Botswana - Keith Jefferis (Transnational Corporations, 2009)
This article reviews the involvement of transnational corporations (TNCs) in the extractive industry of Botswana and the role of government policy that has governed its development. First, it reviews the trends and determinants of TNC involvement in various sub-sectors of mining. Then it assesses the economic, environmental and social impacts of mining, which have been largely positive in Botswana. To identify the factors contributing to the success, the article describes the government policy and involvement in the extractive industry. The article concludes by offering some recommendations.